Penanaman Nilai Moderasi Beragama pada Mata Pelajaran PAI di Madrasah Ibtidaiyah - Prasetyo, Oky Bagas; Pramitha, Devi; Yulianto, Yulianto; Ningsih, Anita Andriya (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
The role of teachers in managing moderate education which truly has the power to create an atmosphere that is conducive to the growth and development of the expected values of religious moderation, is not just a concept contained in certain subjects or also in programs to gain recognition that moderate education has been achieved. The aim of this research is to describe the materials, methods and media in PAI subjects in MI. This type of research is a qualitative descriptive method with case studies, collecting data using interviews, observation and documentation. The results of this research show that, instilling Moderation Values through learning in class VI at MI Miftahul Ulum Disanah Sampang, including, 1) Learning Aqidah Akhlak is carried out using discussion and lecture materials and methods as well as LCD media displaying pictures/videos, 2) Learning Al -Qur'an Hadith is carried out on drill and memorization materials and methods as well as LCD media, laptops 3) Fiqh learning is carried out on demonstration materials and methods and media a) Books b) People's media (teachers and students), Direct media (rice and money) c) Direct media (supplies brought) and posters/pictures, 4) SKI (History of Islamic Culture) learning is carried out using discussion and lecture storytelling materials and methods, as well as audio-visual media